The Reading Comprehension for fourth year primary school pupils (gender and geographical area variables) -A fields study in some primary schools in BOUIRA. - MANCER , Amal; BOUDJEllAL, Souhila (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2026)
The current study aimed to find out the level of reading comprehension in a sample of fourth year pupils in primary school, and to know the differences in their reading comprehension levels, refering to (gender, geographical area). To achieve these goals, the descriptive method was used, as well as the reading comprehension test designed by the researcher EL ATWI (2014), which has four levels as flows (literal level, deductive level, evaluative level then creative level) after being sure of the psychometric properties (credibility and constancy). The sample consisted of (131 pupils); girls and boys of fourth year primary school, who were selected randomly from some primary schools in BOUIRA during the school year (2020/2021). After collecting the data and analysing them using the statistical package for the social science (SPSS), the study found the following results: The level of reading comprehension in the sample is low. There were significant statistical differences at the level of significance (a=0.05) between boys and girls, in the total score of reading comprehension levels 'test, as well as in the deductive level at the level of significance (a=0.01), both in favour of girls. But there were no significant statistical differences found between the two genders in other reading comprehension levels (literal, evaluative, and creative). The lack of statistically significant differences in reading comprehension levels for fourth year pupils attributable to the geographical area variable (town, countryside). The results were interpreted in the light of previous studies, and the study culminated in a number of suggestions.